SPECIALIZING OF THE HEAT TRANSFER COEFFICIENTS FOR SOLUTION OF THE PROBLEM OF THE CYLINDRICAL UNINTERRUPTEDLY-CASTED SLUGS SOLIDIFICATION WITH USING OF EXPERIMENTAL TEMPERATURE DATA OF CRYSTALLIZER IN STEADY CASTING REGIME - A. M. Branovitski; Ju. L. Stanulenis; Ju. A. Lebedinski (Литьë и металлургия, 2005)
The article is dedicated to solving of inverse problem of heat conduction. The simple procedure of searching of the heat transfer coefficients for cylindrical casting on the basis of solution of two-dimensional equation of heat transmission is offered.